2016
DOI: 10.1016/j.jcta.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Equiangular lines in Euclidean spaces

Abstract: We obtain several new results contributing to the theory of real equiangular line systems. Among other things, we present a new general lower bound on the maximum number of equiangular lines in d dimensional Euclidean space; we describe the two-graphs on 12 vertices; and we investigate Seidel matrices with exactly three distinct eigenvalues. As a result, we improve on two long-standing upper bounds regarding the maximum number of equiangular lines in dimensions d=14, and d=16. Additionally, we prove the nonexi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 51 publications
7
112
0
1
Order By: Relevance
“…Greaves, Koolen, Munemasa and Szöllösi [7] obtained the same result (Proposition 3.7) using different methods.…”
Section: Theorem 1 If a Switching Class Of N-vertex Graphs Is A Sssupporting
confidence: 61%
“…Greaves, Koolen, Munemasa and Szöllösi [7] obtained the same result (Proposition 3.7) using different methods.…”
Section: Theorem 1 If a Switching Class Of N-vertex Graphs Is A Sssupporting
confidence: 61%
“…The above discussion proves the following theorem: For n = 22 and each of the intersection patterns z z z ( , , ) = (12, 12, 0), 3 4 5 (13,8,3), (14,4,6), the system of Equations (20) and (21) is the same. This system has the solutions x x x ( , , ) = (1, 3, 6) 11 12 22 and x x x ( , , ) = (2, 6, 2) 11 12 22 .…”
Section: By Solving This System Of Equations We Obtainmentioning
confidence: 68%
“…A computer search showed that there exists no Seidel matrix of order 13 with smallest eigenvalue equal to goodbreakinfix−5 with multiplicity 4 . This proved that B(10,2)goodbreakinfix=12.…”
Section: For Ngoodbreakinfix>10 Ngoodbreakinfix+1goodbreakinfix=boldmentioning
confidence: 97%
“…Proof. Let M = (4t + 3)I + S 2 and let P ∈ O 4t+1 (Z) satisfy (9). We write r i for the ith distinct row of P MP .…”
Section: Proof For the Skew-symmetric Casementioning
confidence: 99%
“…Lemma 5.24 of[9]). Let M be a positive semidefinite {0, ±1}-matrix with constant diagonal entries 1.…”
mentioning
confidence: 99%